The effect of spring coefficients in the dynamic analysis model of the pile foundation structure in Binh Thuan seas, Vietnam - Nguyen Thi Bach, Duong; Nguyen Anh, Dan (Vietnam Journal of Marine Science and Technology, 2021)
Now, the field experiments according to the non-destructive test method are developing widely in diagnostics and verification of structural engineering. To research and apply the impact vibration test, one of these non-destructive methods, the construction of the design dynamic analysis model is significant. The paper goes into research on the formulas to determine the dynamic spring coefficients according to Japanese and Vietnamese standards. Then, apply calculations for dynamic analysis models of pile foundations built in the Binh Thuan sea area. The impact vibration test in the field shows the appropriate formula for calculating the coefficient of dynamic springs in Binh Thuan, Vietnam.